(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2014)
The theoretical ground for the fulfillment of the Peruvian constitution lies in the psychoanalytical theory, particularly in the contributions of Wilfrid Bion and Melanie Klein. From a rather experiential perspective, the author presents the material basis of the Peruvian constitution as a traumatic and conflictive experience founded in opposing views which don´t blend in one single identity based in selfacknowldegment of the duality of ethnical and cultural origin. Analysis develops into criticism of the premises of juridical discourse upon which is based the doctrine of constitutionalism and the ideology of the Constitutional Rule of Law, which are conceived as derivations of idealist rationalism that produces normative fetishism and also that masks exposure of the real and true political constitution.